SISTEM INFORMASI RAWAT JALAN PADA KLINIK BAKTI ASIH BERBASIS WEB - Azmi Darma Wijayanto (2022)
Outpatient is a service process in the health sector which consists of several series of activities. Outpatient services produce a medical record report containing data from the patient's diagnosis at the consultation that has been carried out. This observation was carried out as material for writing a Final Project which aims to determine the patient's outpatient process and patient medical record data at the Bakti Asih Clinic. The purpose of this study is to propose a computerized and structured system for the outpatient service process and the reports of medical colleagues at the Bakti Asih Clinic which are still done manually. In this study, the method used to develop the system is to apply PIECES and Waterfall. From the research, it can be seen that outpatient services are services that consist of an initial process by making a consultation schedule up to the final process, namely consultation with a doctor. The completed outpatient process produces a patient medical record report containing patient data, complaints, diagnoses, and medications needed for the patient. All these activities are still done manually so that there are difficulties in storing and processing existing data.